The Ability of Thai Herbal Household Plant Crude Extracts (Alpinia Galangal) in Growth Inhibition of Mold Aspergillus Flavus and Destruction of AflatoxinB1 - Dungkokkruad, Pinyapach; Jutirak, Jatupol; Wongkamsom, Nutsuda; Kongsee, Pattama; Saichi, Montol; Meesa-ad, Atchariya (European Journal of Sustainable Development, 2017)
AflatoxinB1 (AFB1) produced from mold Aspergillus flavus (A. flavus) contaminated in foods causing in liver cancer. This study aims to inhibit the growth of A. flavus and destroy AFB1 by using the crude extracts in water of Thai herbal household plants such as ginger, galangal, garlic and elephant garlic. Quantity of Free AFB1 was analyzed by ELISA. The results indicated that crude extract of galangal could inhibits the growth of mold at 30.8%, followed by elephant garlic and garlic were at 4.3 and 1.8 %, respectively, while ginger could not inhibit the growth of mold at all conditions. In addition, the concentration at 1:10 w/v with all pH range, especially at regular pH condition of 4.6 was the highest inhibition ability at 73.4%. In addition, galangal crude extract at 1:10 w/v showed the ability to decrease AFB1 at all pH conditions. However, at pH 4.6, the toxin was destroyed within 24 and 72 hrs at 63.4 and 81.9%, respectively. From the results, the crude extracts of galangal could inhibit the growth of A. flavus and destroy the mold toxin as AFB1. Therefore, the application of herbal household plant as food ingredients to prevent the poison from AFB1 is interesting.